Development of a novel cell-based, In-Cell Western/ERK assay system for the high-throughput screening of agonists acting on the delta-opioid receptor - Asghar, Junaid; Latif, Liaque; Alexander, Stephen P. H.; Kendall, David A. (Frontiers in Pharmacology, 2022)
Background: Extracellular signal-regulated kinases (ERKs) are important signaling mediators in mammalian cells and, as a result, one of the major areas of research focus. The detection and quantification of ERK phosphorylation as an index of activation is normally conducted using immunoblotting, which does not allow high-throughput drug screening. Plate-based immunocytochemical assays provide a cheaper and relatively high-throughput alternative method for quantifying ERK phosphorylation. Here, we present optimization steps aimed to increase assay sensitivity and reduce variance and cost using the LI-COR In-Cell Western (I-CW) system in a recombinant CHO-K1 cell line, over-expressing the human delta opioid receptor (hDOPr) as a model. Methods: Cells cultured in 96-well microassay plates were stimulated with three standard/selective DOPr agonists (SNC80, ADL5859, and DADLE) and a novel selective DOPr agonist (PN6047) to elicit a phospho-ERK response as an index of activation. A number of experimental conditions were investigated during the assay development. Key Results: Preliminary experiments revealed a clearly visible edge-effect which significantly increased assay variance across the plate and which was reduced by pre-incubation for 30 minutes at room temperature. ERK phosphorylation was detectable as early as 1 min after agonist addition, with a distinct peak at 3-5 minutes. Optimization of the cell seeding densities showed that 25,000 cells per well have the lowest basal phospho-ERK response and an optimal agonist ERK1/2 signal. Pre-incubation with apyrase (an ATPase) did not reduce the basal or agonist responses. All agonists produced concentration-dependent increases in phospho-ERK activation, and pertussis toxin was able to attenuate these ERK responses. Naltrindole, which is a selective DOPr antagonist, was able to antagonise the DOPr-mediated ERK activation of the ligands. Conclusion: We have developed an optimization protocol and highlighted a number of considerations when performing this high-throughput fluorescence immunocytochemical (ICC) assay measuring ERK phosphorylation in the human DOPr. The optimized protocol was found to be a more conducive option for the screening of delta agonists. This provides a basis for additional assay development to investigate opioid pharmacology. This protocol should be widely applicable for measuring ERK phosphorylation in any cell line and investigating other protein targets in GPCR drug discovery.